Efeitos da penicilina sôbre a regeneração de nervos: Nota preliminar - Orlando Aidar; Constantino Mignone (Arquivos de Neuro-Psiquiatria)
The antibacterial action of penicillin in the presence as well as in the absence of pus, and the innocuousness of its therapeutic concentra-tions in relation to tissues in general, tend to further stimulate the generalized practice of its use in prophylactic and in curative treatment of local infections. This study was undertaken to evaluate the influence of penicillin on nerve regeneration, both under asseptic conditions and in the presence of contamination. This preliminary note refers only to partial results observed in the aseptic material. In these animals, whether treated or not with penicillin, nerve regeneration developed in a like manner, and along the usual general lines.